GIANT HYDRONEPHROSIS DUE TO URETEROPELVIC JUNCTION STENOSIS IN PEDIATRICS: A RARE CASE - Reza Amorga; Daryanto, Besut; Pradana Nurhadi (Indonesian Urological Association, 2024)
Objective: This case report presented giant hydronephrosis (GH) due to Ureteropelvic Junction Stenosis in pediatrics. Case(s) Presentation: A three-year-old boy was admitted with abdominal distension and pain for the last three month. CT scan without contrast of the abdomen showed a left kidney size of 141x 97x 63.5 mm, massive dilatation of the pelvicalyceal system, thinning cortex in the left kidney, and left ureter measurement of 16 mm in diameter. An urgent percutaneous nephrostomy tube (10Fr) was placed in the left kidney for this patient, followed by a pyeloplasty procedure in the next three weeks. The patient was discharged on day five, and the six-month follow-up results were good. Discussion: Giant Hydronephrosis is a rare entity, with less than 500 global cases reported in the literature. The diagnostic approach to suspected hydronephrosis in pediatrics is sonography and may be followed by CT or MRI. Management of giant hydronephrosis requires two stages procedure with percutaneous nephrostomy followed by pyeloplasty. This two-stage method ensure the renal function is preserved. Conclusion: Ureteropelvic Junction Stenosis is a common cause of giant hydronephrosis in pediatrics. Appropriate physical examination and other diagnostic approaches are needed to diagnose patients with giant hydronephrosis and determine the best management. Keywords: Giant hydronephrosis, ureteropelvic junction stenosis, pyeloplasty.